2018
DOI: 10.1155/2018/8739704
|View full text |Cite
|
Sign up to set email alerts
|

Chest Ultrasonography in Modern Day Extreme Settings: From Military Setting and Natural Disasters to Space Flights and Extreme Sports

Abstract: Chest ultrasonography (CU) is a noninvasive imaging technique able to provide an immediate diagnosis of the underlying aetiology of acute respiratory failure and traumatic chest injuries. Given the great technologies, it is now possible to perform accurate CU in remote and adverse environments including the combat field, extreme sport settings, and environmental disasters, as well as during space missions. Today, the usage of CU in the extreme emergency setting is more likely to occur, as this technique proved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 53 publications
0
14
0
1
Order By: Relevance
“…In that study, US examinations was performed at different stages of disease, B-lines showed parallel changes with the clinical severity. However, the unspecific abnormalities realizations in chest CT increase with age, and similarly, the number of chest areas positive for B-lines increases in the elderly [62]. Age-related confounding factors should be taken into consideration in clinical practice in order to avoid misdiagnoses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In that study, US examinations was performed at different stages of disease, B-lines showed parallel changes with the clinical severity. However, the unspecific abnormalities realizations in chest CT increase with age, and similarly, the number of chest areas positive for B-lines increases in the elderly [62]. Age-related confounding factors should be taken into consideration in clinical practice in order to avoid misdiagnoses.…”
Section: Discussionmentioning
confidence: 99%
“…The US could be proposed for the diagnosis or follow up to minimize the risk of cross-infection. Additionally, the US may also play a vital role in areas around the world with limited access to other diagnostic tools, even in austere environments [62].…”
Section: Discussionmentioning
confidence: 99%
“…Medical interventions in extreme conditions most often require a combination of rescue and medical skills and prehospital medicine. Expanded care protocols are an invaluably useful tool in extreme situations, which can be continuously developed by learning and identifying risk factors (30).…”
Section: Discussionmentioning
confidence: 99%
“…Damit ist Ultraschall überall verfügbar und hat seine diagnostischen Möglichkeiten auch unter extremen Bedingungen, z. B. auf Schlachtfeldern, bei Expeditionen und sogar im All unter Beweis gestellt [1].…”
Section: Point-of-care-ultraschall In Der Intensiv-und Notfallmedizinunclassified